A New and Generalized Structure of MLI Topology with Half-bridge Cell with Minimum Number of Power Electronic Devices. Issue 2 (4th March 2021) - Mahato, Bidyut; Majumdar, Saikat; Vatsyayan, Sambit; Jana, K. C.
Abstract : Rapid developments in the field of high-power, high-voltage applications have led to a tremendous increase in the popularity and utility of multilevel inverters. The requirement of reduced harmonics coupled with an ever-increasing demand for clean and renewable energy sources has led to a great interest in the multilevel inverter. This paper presents a novel architecture of a single-phase multilevel inverter that utilizes fewer power electronic switches and driver circuits than various popular multilevel inverter circuits. The design presented is generalized in nature, thereby allowing for the generation of any number of levels in the output voltage. The working and modes of operation of the 9-level symmetrical configuration of the proposed topology is extensively elaborated. Simulation results from MATLAB Simulink as well as real-time hardware results have been included to verify the existence and proper working of the proposed 9-level symmetrical and 15-level asymmetrical inverter. Comparison results with other discussed configurations are also included to further establish the advantages possessed by the proposed circuit.